The effect of using the circular training and the stations techniques in developing some physical abilities and Basic skills for the Goalkeepers of football . from 15-16 years - Jaleel, Qahtan; Radhi, Saleh (Journal of Physical Education, 2008)
The Aims of the Research ; The acquaintance of the effect of using with which technique is the suitable one in developing some physical abilities and Basic skills for Goalkeepers of football , it has been used the empirical style for its sutabilty with the nature of the research . the sample consists of (16) players who belong to the Training center in Baghdad . they were divided in to two equal groups , one of them uses the circular training technique , while the other uses the station technique . on the other hand , this chapter dealt with the ways , tools , the choices of suitable test of physical abilities and basic skills of football , the consulting experiments and how value the program and the statistical ways . Conclusions; it there are spiritual dissimilarities for the bodily test in the skill-tests. by the groups that follows the circular training technique . while find – there are spiritual dissimilarity – es for the post-tests in the bodily tests by the groups that follows he stations technique . the researches are Recommendations : Encourage the trainers for using the circular and stations techniques because of their effect up on the skillfully and bodily aspects being away from the classical styles